2019
DOI: 10.1186/s42506-019-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the psychometric properties of the Arabic version of the Groningen Frailty Indicator among Lebanese elderly people

Abstract: Background: The levels of frailty are anticipated to increase as a result of population aging. A valid instrument is required to detect individuals at high risk of frailty. The present research aimed to assess feasibility, reliability, and construct validity of the Arabic version of Groningen Frailty Indicator (GFI) in urban and rural populations in South Lebanon.Methods: During 2015, a cross-sectional study, which enrolled 390 community-dwelling individuals aged 65 years and above, was conducted in urban and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…According to the results, frailty was more common in females, which was consistent with the findings of previous studies (23,25,(28)(29)(30)(31). In a study carried out by Thompson et al in Australia, the prevalence of frailty in females was reported to be twice that of males (31).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…According to the results, frailty was more common in females, which was consistent with the findings of previous studies (23,25,(28)(29)(30)(31). In a study carried out by Thompson et al in Australia, the prevalence of frailty in females was reported to be twice that of males (31).…”
Section: Discussionsupporting
confidence: 91%
“…In the same vein, low education level was significantly associated with the prevalence of frailty in older adults. This finding is consistent with the results of other studies in the literature (21,22,25,34,35); however, it is not in line with the findings of a study conducted in Belgium (36). Franse et al reported the education level as one of the most consistently socioeconomic characteristics associated with frailty, morbidities, and self-rated health in adults aged 55 years and older (35).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations